SOSIALISASI DAN REHABILITASI EKOSISTEM MANGROVE DI DESA BUANO SELATAN SERAM BARAT MALUKU - Irwanto Irwanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2022)
As a component of the coastal ecosystem, mangroves play an important role, both in maintaining coastal productivity and in supporting the human lives especially of the surrounding communities. The rehabilitation of the mangrove ecosystems in South Buano Village, West Seram, was the program of the Maritime Affairs and Fisheries Service of Maluku Province, which involved the participation of the local communities. The socialization was carried out at the South Buano District Office on December 6th, 2021, attended by the Buano Village communities. The participants, who attended the meeting, came from various age levels, including parents and children. Mothers and school-age children dominated the majority of the participants. The involvement of the community in this mangrove rehabilitation was important because they would gain the awareness in maintaining the sustainability of the mangrove ecosystem. Mangrove tree planting that involves school age children would provide knowledge and could foster a sense of love for mangroves since the early age.